STRUKTUR HISTOLOGI DUODENUM, JEJENUM, DAN ILEUM SAPI BALI - Werdi Susari, Ni Nyoman; Eka Setiasih, Ni Luh; Suwiti, Ni Ketut (Jurnal Veteriner; Vol 10 No 1 (2009))
A study to find out the histological structures of small intestine (ie. duodenum, jejunum, and ileum) of bali cattle have been carried out. A total of 20 small intestines were collected from the abattoir at Pesanggaran, Denpasar Bali. Histological examinations were performed on Haematoxyline Eosin stained small intestines slides. The duodenum, jejunum and ileum of the small intestines have four mucosa membranes: i) mucosa membrane, ii) sub mucosa membrane, iii) muscular membrane and, iv) serous membrane. The average thickness of mucosa membrane of duodenum, jejunum and ileum was 36,3±13,5 mm; 29,9±3,1 mm; and 38,8±11,9 mm, respectively. Each part has villi with an average length of 27,5±8,3 mm; 20,1±3,7 mm; and 18,5±4,3 mm, respectively. This mucosa membranes consist of single columnar epithelium, muscularis mucosa, and lamina propria. The average thickness of sub mucosa membrane was 47,3±15,3 mm; 10,4±2,6 mm; and 16,9±5,6 mm, respectively. Sub mucosa membrane consisted of connective tissue. The average thickness of muscular membrane was 46,9±8,8 mm; 28,1±5,1 mm; and 62,4±11,3 mm, respectively, which consisted of circular and longitudinal smooth muscle. The average thickness of serous membrane was 19,9±3,1 mm; 11,9 ±3,0 mm; and 12,1±3,6 mm, respectively, which consisted of mainly connective tissue. Goblet cells were seen through all the epithel of small intestines with the highest number seen in the ileum. Specific structure of duodenum, jejunum, and ileum which is Brunner’s glands in the sub mucosa membranes of duodenum, circular plicae in the jejunum and mesenteric gland in the ileum were also observed.
Keywords: bali cattle, small intestine, duodenum, jejunum, ileum